Effect of stoichiometric conditions and growth mode on threading dislocations filtering in AlN/c-Al2O3 templates grown by PA MBE. (February 2020) - Nechaev, D.V.; Koshelev, O.A.; Ratnikov, V.V.; Brunkov, P.N.; Myasoedov, A.V.; Sitnikova, A.A.; Ivanov, S.V.; Jmerik, V.N.
Abstract: AlN/ c- Al2 O3 templates were grown by plasma-assisted molecular beam epitaxy using migration enhanced epitaxy (MEE) and metal modulated epitaxy (MME) employed for consequent growing the nucleation and buffer layers (NL and BL). Structural quality and stress evolving were compared using in situ stress measurements, x-ray diffraction, transmission and atomic force microscopies. Optimization of MEE mode of NL led to a high degree of initial nuclei coalescence and the weak tensile stress (<0.35 GPa) in the template. The optimal stoichiometric conditions were found for a double-stage MME of BL. During the first stage with the aluminum to active nitrogen flux ratio F Al / F N* =1.1 at 780 °C, the most effective bending of both screw and edge threading dislocations occurs, followed by their efficient filtration. This bending in the stretched BL is explained by the coarse grain AlN morphology, which can be smoothed dramatically during the top BL growth at higher temperature of 850 °C and F Al / F N* =2.1. Highlights: Nanopatterning of AlN/ c- Al2 O3 interface depends on mode of migration enhance epitaxy used for nucleation layer growth. Most efficient tilt of threading dislocations in AlN layers is observed at slightly Al-enrichment of metal-modulated epitaxy. The bending of threading dislocations in grained layers is explained by image forces pushing dislocations to the side facets.